Lage und Verteilung der Internetbetriebe in der Bundesrepublik Deutschland - Kickner, Susanne (ERDKUNDE, 2006)
It is widely accepted that technological innovations affect regional economic growth. This paper analyzes the spatial distribution of firms concerned with Internet production and services in Germany. The locations of these – most probably young – firms were studied on the basis of address data on municipality level for the years 1997, 1999 and 2002, using a Geographical Information System. Results indicate a high concentration of firms in certain large agglomerations. Empirical indices show that the presence of a sufficient number of young male people, the contact to other entrepreneurs, a high quality of life and parity power are strong related to the number of internet firms. Centres of highest concentration, which can be seen as sustainable regional innovation systems, are mostly situated in the south and south-west of West Germany whilst internet centres are still lacking in East Germany.